In vitro Propagation of the Biodiesel Plant Jatropha curcas L. (Plant Tissue Culture and Biotechnology, 2009)
The biodiesel plant, Jatropha curcas L. was micropropagated using nodal explants on MS supplemented with BAP (1.5 mg/l), Kn (0.5 mg/l) and IAA (0.1 mg/l). Somatic embryos were induced directly from green cotyledon explants on MS fortified with 2 mg/l of BAP. The results of histological studies showed that several layers of meristematic cells participated in the formation of somatic embryos. Rooting was effectively achieved on MS supplemented with IAA at 1.0 mg/l. The subsequent hardening experiment showed that the commercial medium containing a mixture of decomposed coir waste, perlite and organic compost in the ratio of 1:1:1 by volume was most effective, 80% plantlets survived. Key words: Jatropha curcas, Nodal explants, Cotyledons, Somatic Embryos, Multiple shoot formation D.O.I. 10.3329/ptcb.v17i2.3234 Plant Tissue Cult. & Biotech. 17(2): 137-147, 2007 (December)